Ответы и объяснения

2013-03-23T11:57:47+00:00

1) \ (\frac{a}{a-b}-\frac{a}{a+b})*\frac{a+b}{a}=\frac{a(a+b)-a(a-b)}{(a+b)(a-b)}*\frac{a+b}{a}=\\ \\ =\frac{a^2+ab-a^2+ab}{(a+b)(a-b)}*\frac{a+b}{a}=\frac{2ab}{(a+b)(a-b)}*\frac{a+b}{a}=\frac{2b}{a-b}\\ \\ 3)(\frac{a}{c}+\frac{c}{a}-2)*\frac{1}{a-c}=\frac{a^2+c^2-2ac}{ac}*\frac{1}{a-c}=\frac{(a-c)^2}{ac}*\frac{1}{a-c}=\frac{a-c}{ac}\\ \\ 5)(\frac{3c+1}{c-1}+c)*\frac{1}{c+1}=\frac{3c+1+c^2-c}{c-1}*\frac{1}{c+1}=\frac{c^2-2c+1}{c-1}*\frac{1}{c+1}=\\ \\ =\frac{(c-1)^2}{c-1}*\frac{1}{c+1}=\frac{c-1}{c+1}\\

 

7) (\frac{c}{a-c}-\frac{c}{a})*\frac{a^2}{c^2}=\frac{ca-ca+c^2}{a(a-c)}*\frac{a^2}{c^2}=\frac{c^2}{a-c}*\frac{a}{c^2}=\frac{a}{a-c}\\ \\ 9) (\frac{b}{b+a}-\frac{b-a}{b}):\frac{a}{b}=\frac{b^2-b^2+a^2}{b(b+a)}*\frac{b}{a}=\frac{a^2}{b+a}*\frac{1}{a}=\frac{a}{b+a}

 

Все остальное аналогично. Попробуй сама